New species and records of Metatarsonemus (Acari: Tarsonemidae) from Central and South Americas - Guimarães Sousa, André Silva (2022)
The family Tarsonemidae (Acari: Prostigmata) exhibits a high diversity of feeding habits and morphological structures, which allow them to be successful in many habitats. In Costa Rica, the Mesoamerican forest is a biome that includes all tropical and subtropical natural plant formations with high biodiversity. In Brazil, Theobroma cacao L. (Malvaceae) is cultivated under the canopies of larger trees, in a shaded plantation system called cabruca. Two new Metatarsonemus species are described from Brazilian cabruca agroforest. New records for the genus from Mesoamerica, Atlantic Forest and cabruca agroforest are presented. A key to the species of Metatarsonemus of the world is included.